Carles Salvador i la reivindicació de l’ús social de la llengua catalana - Pérez i Moragón, Francesc (Caplletra. Revista Internacional de Filologia, 2015)
Carles Salvador described himself as «a politician of language». Already at an early age, he staunchly defended the right to speak Catalan in the Valencian Country at every level, beginning in primary school. Pérez i Moragón situates this posture within the Valencian linguistic panorama in an era characterized by the dictatorship of Primo de Rivera, the Second Republic, and the Franco regime.